1961
DOI: 10.1002/jcp.1030570209
|View full text |Cite
|
Sign up to set email alerts
|

The exchange of radioactive magnesium in erythrocytes of several species

Abstract: A previous publication (Rogers and Mahan, '59) has described the exchange of radioactive magnesium in various tissues of the rat. It was found that there are two principal exchange rates, one with a turnover time of 1.2 hours and another with about 25 hours. In myocardium, liver and kidney, only the fast component was apparent and the specific activity of the tissue magnesium reached that of the plasma magnesium in three hours. In the other tissues studied (brain, skeletal muscle, testes and red cells), more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Our present results confirm their findings [14] that a single dialysis has no demonstrable effect on erythrocyte magnesium con centrations, unlike the concurrent plasma levels. This finding accords with the orthodox view that erythrocytes are relatively impermeable to magnesium ions [20,26], the immediate changes during one dialysis being seen only in the plasma magnesium.…”
Section: Plasma and Erythrocyte Magnesiumsupporting
confidence: 80%
“…Our present results confirm their findings [14] that a single dialysis has no demonstrable effect on erythrocyte magnesium con centrations, unlike the concurrent plasma levels. This finding accords with the orthodox view that erythrocytes are relatively impermeable to magnesium ions [20,26], the immediate changes during one dialysis being seen only in the plasma magnesium.…”
Section: Plasma and Erythrocyte Magnesiumsupporting
confidence: 80%
“…If anything, however, red cells seem to lose magnesium as they age (Bernstein, 1959). Rogers (1961) and Ginsburg et al (1962) have shown that 28Mg exchanges extremely slowly between medium and red cells which suggests that the membrane has a low permeability to magnesium. Moreover, it has been shown here that red cell magnesium content does not depend on the composition of the media, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane of human red blood cells has such a low permeability to magnesium (Rogers, 1961;Ginsburg, Smith, Ginsburg, Reardon & Aikawa, 1962) that it was not possible until recently to alter the magnesium content of red cells in a controllable manner without disruption of the cell membrane. The dependence of fundamental physiological functions on the concentration of magnesium was therefore studied using reconstituted ghosts (Bodemann & Hoffman, 1976) and broken membrane fragments (Dunham & Glynn, 1961;Schatzmann, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cells from many species have a very low Mg permeability [13,25]. For instance, Mg efflux from fresh human and chicken red blood cells is too low to measure easily [1,18,24].…”
Section: Introductionmentioning
confidence: 99%